2005
DOI: 10.1097/01.psy.0000151485.38411.36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treating Exhaustion in Angioplasty Patients on New Coronary Events: Results of the Randomized Exhaustion Intervention Trial (EXIT)

Abstract: A behavioral intervention in PCI patients has a beneficial effect on feelings of exhaustion. It could not be demonstrated that the intervention reduces the risk of a new coronary event within 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 32 publications
4
72
0
Order By: Relevance
“…In the current study, patients with a cardiac history prior to the referral event reported impaired health status compared to patients without a cardiac history. These findings are in line with the Exhaustion Intervention Trial (EXIT), which showed that percutaneous coronary intervention patients with a cardiac history prior to the referral event were less likely to benefit from a behavioral intervention program designed to improve symptoms of vital exhaustion [34]. Secondary analyses indicated that, in particular, patients with two or more previous cardiac events prior to the index percutaneous coronary intervention benefited less from the intervention.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the current study, patients with a cardiac history prior to the referral event reported impaired health status compared to patients without a cardiac history. These findings are in line with the Exhaustion Intervention Trial (EXIT), which showed that percutaneous coronary intervention patients with a cardiac history prior to the referral event were less likely to benefit from a behavioral intervention program designed to improve symptoms of vital exhaustion [34]. Secondary analyses indicated that, in particular, patients with two or more previous cardiac events prior to the index percutaneous coronary intervention benefited less from the intervention.…”
Section: Discussionsupporting
confidence: 73%
“…An effect size ranging from 0.00 to 0.20 is negligible to small, 0.20 to 0.50 small to moderate, 0.50 to 0.80 large, and >0.80 very large [33]. Cardiac history prior to the referral event was chosen as comparison, since this variable previously has been shown to moderate the effectiveness of a behavioral intervention in vitally exhausted patients undergoing a percutaneous coronary intervention [34]. A post-hoc power analysis showed that, with an assumed effect size of 0.20, α=0.05, and a power of 95%, a sample size of 327 patients was required to detect statistical differences in SF-36 scores preand post-cardiac rehabilitation (repeated measures design, within-between interaction).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For example, the inappropriate use of factor analytic techniques with skewed/binary items, a misinterpretation of Cronbach's a to indicate unidimensionality, the use of simple correlations to decide whether constructs are 'moderately' related, or a choice of scales which have no overlapping symptoms. 5,10,17,21 In the present study, internal consistencies were very good for the original depression and vital exhaustion scales, which then correlated at a level which indicated only 18% shared variance. Such correlational results, however, can simply be indicative of different levels of severity of a single trait -as borne out by the subsequent Mokken results presented herein.…”
Section: Discussionsupporting
confidence: 53%
“…13,23 Such a tipping point would also give interventions to improve prognosis a definite target, rather than a reduction in an overall scale score by a set number of points. While interventions have been demonstrated to reduce symptoms of depression in cardiac patients, 21,24 it is unclear which symptoms were reduced as total scale scores of non-hierarchical scales have heretofore been adopted as outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Post-PCI patients often experience new coronary events within the first 6 months after PCI. 10 These early events are mainly caused by factors related to the procedure itself, such as recoil of the vessel wall and neointimal hyperplasia. Late events, that is, events occurring after 6 months, are usually related to new lesions elsewhere in the coronary system.…”
mentioning
confidence: 99%